2018
DOI: 10.1371/journal.ppat.1006869
|View full text |Cite
|
Sign up to set email alerts
|

HIC1 links retinoic acid signalling to group 3 innate lymphoid cell-dependent regulation of intestinal immunity and homeostasis

Abstract: The intestinal immune system must be able to respond to a wide variety of infectious organisms while maintaining tolerance to non-pathogenic microbes and food antigens. The Vitamin A metabolite all-trans-retinoic acid (atRA) has been implicated in the regulation of this balance, partially by regulating innate lymphoid cell (ILC) responses in the intestine.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…ILC3s respond to food-induced expression of neuropeptide vasoactive intestinal peptide (VIP) allowing them to maintain epithelial barrier integrity [90]. Dietary nutrient deficiencies, such as vitamin A or vitamin D deficiency, leads to a loss of ILC3s in the gut [91][92][93], while ILC2 number and effector function are enhanced by increased FAO and acquisition of long-chain fatty acids [61]. Dietary nutrient oversupply of fat, which leads to obesity, results in the hypertrophy of adipocytes, limiting their nutrient and oxygen availability and resulting in a sustained stress response in both adipocytes and stromal cells [94][95][96].…”
Section: Environmental Changes In Host Metabolism Influence Ilc Biologymentioning
confidence: 99%
“…ILC3s respond to food-induced expression of neuropeptide vasoactive intestinal peptide (VIP) allowing them to maintain epithelial barrier integrity [90]. Dietary nutrient deficiencies, such as vitamin A or vitamin D deficiency, leads to a loss of ILC3s in the gut [91][92][93], while ILC2 number and effector function are enhanced by increased FAO and acquisition of long-chain fatty acids [61]. Dietary nutrient oversupply of fat, which leads to obesity, results in the hypertrophy of adipocytes, limiting their nutrient and oxygen availability and resulting in a sustained stress response in both adipocytes and stromal cells [94][95][96].…”
Section: Environmental Changes In Host Metabolism Influence Ilc Biologymentioning
confidence: 99%
“…In addition, misregulation of either Wnt or TGFβ greatly impacts Pitx2 levels, suggesting that the different pathways interact for proper signaling control 89,97. Potential crosstalk is observed in the upregulation of genes associated with RA signaling ( Sox6 and Hic1 ), which suppress Wnt signaling 119123. The Wnt activating genes ( Prrx2 and Hmga2 ) are upregulated by TGFβ,51,52 and we observed that Hmga2 localizes to the corneal epithelium where Wnt expression is dominant 56…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, CD4 + cells are the main source of IL-22 in the late phase of infection [ 74 , 75 ]. Activation of ILC3 during C. rodentium infection is mediated by many pathways including specific activation of ILC3 surface receptors [ 59 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ], diet- and bacteria-derived metabolites [ 85 , 86 , 87 , 88 , 89 , 90 , 91 ] and interposed phagocytes [ 92 , 93 , 94 , 95 , 96 ].…”
Section: Infections Of the Gastrointestinal Tractmentioning
confidence: 99%
“…Recently, it has been also shown that ILCs express the transcriptional repressor, hypermethylated in cancer 1 (HIC1, ZBTB29), which is regulated by vitamin A. Lack of HIC1 abolished IL-22-expressing ILC3 and increased susceptibility to C. rodentium infection [ 88 ]. In contrast to vitamin A, vitamin D has been shown to negatively regulate ILC3 in C. rodentium infection.…”
Section: Infections Of the Gastrointestinal Tractmentioning
confidence: 99%